2016
DOI: 10.1111/pcmr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Water Buffalo (Bubalus bubalis) as a spontaneous animal model of Vitiligo

Abstract: Vitiligo is a multifactorial acquired depigmenting disorder. Recent insights into the molecular mechanisms driving the gradual destruction of melanocytes in vitiligo will likely lead to the discovery of novel therapies, which need to be evaluated in animal models that closely recapitulate the pathogenesis of human vitiligo. In humans, vitiligo is characterized by a spontaneous loss of functional melanocytes from the epidermis, but most animal models of vitiligo are either inducible or genetically programmed. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…A total number of 734 participants (375 of which were diagnosed with vitiligo) were included across all studies: 128 (63 with vitiligo, 49.2%) from Atas et al [ 19 ], 191 (102 with vitiligo, 53.4%) from Sallam et al [ 20 ], 200 (100 with vitiligo, 50%) from Sharma et al [ 27 ], 65 (35 with vitiligo, 53.8%) from Singh et al [ 28 ], 150 (75 with vitiligo, 50%) from Sinha et al [ 29 ], and 310 (155 with vitiligo, 50%) from Tanacan et al [ 30 ]. The type of vitiligo varied across papers, with both segmental and nonsegmental types examined in 3 studies [ 19 , 20 , 30 ]; 1 paper exclusively studied nonsegmental types [ 27 ], and 2 studies did not specify the type of vitiligo the patients were diagnosed with [ 28 , 29 ]; 3 studies reported the duration of vitiligo (in years): 9.5 (SD 8.1) [ 19 ], 5.29 (SD 6.8) [ 20 ], and 43.5 (SD 10.5) [ 27 ]; however, the duration was statistically significant across these studies ( P =.03). The diagnostic criteria for MetS also varied among studies, with 4 studies using NCEP ATP III criteria [ 19 , 27 , 29 , 30 ] and 2 using IDF criteria [ 20 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total number of 734 participants (375 of which were diagnosed with vitiligo) were included across all studies: 128 (63 with vitiligo, 49.2%) from Atas et al [ 19 ], 191 (102 with vitiligo, 53.4%) from Sallam et al [ 20 ], 200 (100 with vitiligo, 50%) from Sharma et al [ 27 ], 65 (35 with vitiligo, 53.8%) from Singh et al [ 28 ], 150 (75 with vitiligo, 50%) from Sinha et al [ 29 ], and 310 (155 with vitiligo, 50%) from Tanacan et al [ 30 ]. The type of vitiligo varied across papers, with both segmental and nonsegmental types examined in 3 studies [ 19 , 20 , 30 ]; 1 paper exclusively studied nonsegmental types [ 27 ], and 2 studies did not specify the type of vitiligo the patients were diagnosed with [ 28 , 29 ]; 3 studies reported the duration of vitiligo (in years): 9.5 (SD 8.1) [ 19 ], 5.29 (SD 6.8) [ 20 ], and 43.5 (SD 10.5) [ 27 ]; however, the duration was statistically significant across these studies ( P =.03). The diagnostic criteria for MetS also varied among studies, with 4 studies using NCEP ATP III criteria [ 19 , 27 , 29 , 30 ] and 2 using IDF criteria [ 20 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The type of vitiligo varied across papers, with both segmental and nonsegmental types examined in 3 studies [ 19 , 20 , 30 ]; 1 paper exclusively studied nonsegmental types [ 27 ], and 2 studies did not specify the type of vitiligo the patients were diagnosed with [ 28 , 29 ]; 3 studies reported the duration of vitiligo (in years): 9.5 (SD 8.1) [ 19 ], 5.29 (SD 6.8) [ 20 ], and 43.5 (SD 10.5) [ 27 ]; however, the duration was statistically significant across these studies ( P =.03). The diagnostic criteria for MetS also varied among studies, with 4 studies using NCEP ATP III criteria [ 19 , 27 , 29 , 30 ] and 2 using IDF criteria [ 20 , 28 ]. Two studies [ 27 , 30 ] took into consideration social risk factors such as alcohol and smoking use; Sharma et al [ 27 ] report no significant association between smoking ( P =.31) or alcohol ( P =.28) and the development of MetS in patients with vitiligo.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the apps that purported to reduce anxiety symptoms did not include any link to peer-reviewed literature or the evidence base. Other reviews have reported the lack of provision of evidence-based app content [28,35,36,56]. Although web-based mindfulness and CBT approaches have been reported as effective in reducing anxiety and other mental health concerns in perinatal populations [57,58], evidence-based information was not presented in the apps.…”
Section: Locating and Evaluating Appsmentioning
confidence: 99%
“…Health apps for use in pregnancy or to support individuals with anxiety symptoms have been assessed as having poor quality [26][27][28], lacking evidence-based content [29], and being ineffective or potentially harmful [30]. Other reviews of pregnancy apps have reported that apps contained little or no pregnancy-specific information [26] and contained information that was potentially harmful for pregnant women [31].…”
Section: Introductionmentioning
confidence: 99%
“…Depigmented animals are excellent models for investigation of the genetic determination of the corresponding morphological traits, and studies of such animals may provide evolutionary and mechanistic insights into animal and human chromatophore-related diseases (e.g., vitiligo, albinism, and melanoma). Although recent investigations have deepened our understanding of these diseases, many questions surrounding their initiation and progression remain to be answered ( 13 ), and proper animal models are important as a means of studying their pathogenesis and facilitating the discovery and evaluation of therapeutic interventions ( 18 ). The Chinese giant salamander (Cryptobranchidae: Andrias davidianus ) is the largest extant amphibian species ( 19 ).…”
Section: Introductionmentioning
confidence: 99%